Comparison of anti-biofilm and cytotoxic activity of Ag/AgO, Ag/Ag2O, and Ag/AgCl nanocomposites synthesized using stem, leaf, and fruit pericarp of Prunus mahaleb L - Zahra Dashtizadeh; Fereshteh Jookar Kashi (Scientific Reports)
Abstract The green synthesis of nanoparticles using plant-derived biomolecules provides an eco-friendly, cost-effective, and scalable approach with minimal environmental impact. The present study investigates the green synthesis of silver-based nanocomposites (AgNPs) using aqueous extracts from various anatomical parts of the stem, leaf, and fruit pericarp of Prunus mahaleb L., to assess their physicochemical properties, antibiofilm performance, and cytotoxic potential. Unlike conventional single-part plant synthesis, our multi-part approach introduces a diverse array of phytoconstituents, enhancing nanoparticle stability, morphological homogeneity, and functional bioactivity. UV–Vis spectroscopy revealed surface plasmon resonance (SPR) peaks at 426.00 nm, 414.00 nm, and 426.50 nm for Ag/AgO, Ag/Ag₂O, and Ag/AgCl nanocomposites, respectively, indicating successful nanoparticle formation. FT-IR confirmed the presence of functional groups involved in reduction and stabilization. XRD patterns validated the crystalline nature of the nanocomposites, with Ag/AgO displaying the smallest crystallite size. SEM analyses showed spherical morphologies with average sizes of 43.55 nm (stem), 45.44 nm (leaf), and 61.66 nm (fruit pericarp), consistent with EDX-determined silver contents of 9.01%, 42.34%, and 18.25%, respectively. In bioactivity assays, Ag/AgO and Ag/Ag₂O nanocomposites demonstrated moderate biofilm inhibition and exhibited pronounced cytotoxicity in brine shrimp lethality assay (LC₅₀ = 28 ± 0.42 µg/ml and 28 ± 0.40 µg/ml, respectively). In contrast, the Ag/AgCl nanocomposite synthesized from the fruit pericarp extract showed strong anti-biofilm activity, with inhibition percentages reaching up to 145.71%, though it exhibited lower cytotoxicity (LC₅₀ > 300 µg/ml). These results demonstrate the potential of P. mahaleb-mediated nanocomposites as promising candidates for biomedical applications, particularly in the development of novel antimicrobial and anticancer agents.